1998
DOI: 10.1002/hep.510280408
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of α1-6 fucosyltransferase in human hepatoma tissues: A possible implication for increased fucosylation of α-fetoprotein

Abstract: The ␣1-6 fucosylated ␣-fetoprotein (AFP) present in serum of patients with hepatocellular carcinoma (HCC) has been employed for the differential clinical diagnosis of HCC from chronic liver diseases. The molecular mechanism by which this alteration occurs, however, remains largely unknown. To address this issue, we purified GDP-L-Fuc:Nacetyl-␤-D-glucosaminide ␣1-6 fucosyltransferase (␣1-6 FucT), an enzyme involved in the ␣1-6 fucosylation of N-glycans from porcine brain, as well as from a human gastric cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
82
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(88 citation statements)
references
References 30 publications
(36 reference statements)
4
82
2
Order By: Relevance
“…We also isolated a genomic clone for the human α1,6FucT gene (FUT8) and used this to map the gene on human chromosome 14q24.3 by fluorescence in situ hybridization (Yamaguchi et al, 1999). Northern blot analyses have shown that a good correlation exists between the increased α1,6FucT activities in hepatocellular carcinomas and the elevated levels of the FUT8 mRNA Noda et al, 1997Noda et al, , 1998. This supports the view that the FUT8 is certainly responsible for the increased fucosylation which is associated with hepatocellular carcinoma.…”
Section: Introductionsupporting
confidence: 55%
“…We also isolated a genomic clone for the human α1,6FucT gene (FUT8) and used this to map the gene on human chromosome 14q24.3 by fluorescence in situ hybridization (Yamaguchi et al, 1999). Northern blot analyses have shown that a good correlation exists between the increased α1,6FucT activities in hepatocellular carcinomas and the elevated levels of the FUT8 mRNA Noda et al, 1997Noda et al, , 1998. This supports the view that the FUT8 is certainly responsible for the increased fucosylation which is associated with hepatocellular carcinoma.…”
Section: Introductionsupporting
confidence: 55%
“…Previously, the increased FUT8 mRNA level in the liver was also shown in patients with chronic hepatitis and liver cirrhosis (34). In the liver of patients with type 2 DM, various changes are caused by insufficient insulin action (37).…”
Section: Discussionmentioning
confidence: 89%
“…␣1,6-Fucosyltransferase (FUT8) is the only reported enzyme that catalyzes ␣1,6-fucosylation in mammals (29). Elevated expression of FUT8 was observed in human ovarian serous adenocarcinoma (40), hepatoma, and liver cirrhosis (34) and was linked to tumor size and lymph node metastasis in thyroid papillary carcinoma (20). Recently, the function of ␣1,6-fucosylation was analyzed using FUT8-deficient mice (45).…”
mentioning
confidence: 99%
“…An N-glycan profiling study identified novel N-glycan structures in serum as prognostic markers of hepatocellular carcinoma (11). In addition, a-1,6-fucosyltransferase can generate fucosylated a-fetoprotein (AFP), which provided a more accurate diagnosis of hepatocellular carcinoma from chronic liver diseases (12,13). However, changes in O-linked glycosylation have been overlooked in the past.…”
Section: Introductionmentioning
confidence: 99%